Manhaj Muqtaroh Li Ta’limil Lughah Al Arabiyah Min Khilali Al Kalimat Al Malawiah Zatul Asli Arabi Min Qamus Daya Harfu (K-M) Numuzajan - Fachrirazi; Mulyadi (Mauriduna: Journal of Islamic Studies, 2020)
هدفت هذه الدراسة إلى معرفة واكتشاف الكلمات ذات أصل عربي في قاموس دايا من حرف K إلى حرف M نموذجا، ثم تصميمها إلى المنهج المقترح لغرض تسهيل معلمين لتعليم اللغة العربية للملايويين. تواصل الباحث إلى هذه الدراسة في الناتجتين؛ أولهما وجود الكلمات ذات أصل عربي في قاموس دايا وعددها وصل نحو 184 كلمة من حرف K إلى حرف M، وثانيهما أنه من خلال هذه الكلمات الملايوية يمكن تسهيل عملية التعليم والتعلم، ويكون ذلك في تصميم المنهج المناسب لهم،وذلك باستخدام تلك الكلمات التي لها أصل عربي لتعليم اللغة العربية. وتضمنت هذه الدراسة المهارات الأربع ما عدا الكتابة، من الحوارات، والمفرادات، والتدريبات، والنصوص، وكذلك الأساليب والطرق في تعليم اللغة العربية للملايويين. This study aims to know and find Malay words derived from Arabic in the DAYA dictionary from the letter K to the letter M. This research helps students learn Arabic indirectly using their language, so they can learn, memorize vocabulary and understand its meaning more easily. Researchers found two results: the first is the presence of Arabic words in the Daya dictionary and the number reaches around 184 words from the letter K to the letter M, and the second is through these Malay words, the teaching and learning process can be facilitated in designing a curriculum appropriate for the Malay community, and that is by using the words of Malay Language which originated from Arabic making it easier for Malay people to learn Arabic. This study includes four skills except for writing skills, and in them consists of; dialogues, vocabulary, exercises, and texts, as well as methods and methods in teaching Arabic to Malay beginners.